2021
DOI: 10.1007/s42979-020-00422-6
|View full text |Cite
|
Sign up to set email alerts
|

Robust Detection of COVID-19 in Cough Sounds

Abstract: , otherwise known as the coronavirus, has precipitated the world into a pandemic that has infected, as of the time of writing, more than 10 million persons worldwide and caused the death of more than 500,000 persons. Early symptoms of the virus include trouble breathing, fever and fatigue and over 60% of people experience a dry cough. Due to the devastating impact of COVID-19 and the tragic loss of lives, it is of the utmost urgency to develop methods for the early detection of the disease that may help limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 64 publications
3
58
0
Order By: Relevance
“…Several studies have already explored the usability of voice, cough and breathing for detection and screening of COVID-19 [ [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. Crowdsourced dataset of cough and breathing samples is collected and used for distinguishing between individuals tested positive and negative to COVID-19, as well as participants diagnosed with asthma [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already explored the usability of voice, cough and breathing for detection and screening of COVID-19 [ [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. Crowdsourced dataset of cough and breathing samples is collected and used for distinguishing between individuals tested positive and negative to COVID-19, as well as participants diagnosed with asthma [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…(CV, cross validation, Acc, accuracy, Spe, specificity, Rec, recall, F1, F1-score). Authors Methods Number of Data Performance(%) Pahar et al (2020) [ 43 ] MFCCs, log energy, zero-crossing rate 1171 Rec=93.0 Spe=95.0 and kurtosis/ResNet50 Acc=98.0 Laguarta et al (2020) [ 18 ] MFCCs/3 parallel ResNet50 5320 Rec=98.5 Spe=94.2 Sharma et al (2020) [ 20 ] MFCCs, and other spectral measurements/ 941 Acc=67.7 random forest Mouawad et al (2020) [ 21 ] MFCCs and RQA/XGBoost 1927 Acc=97.0 F1=62.0 Pal ve Sankarasubbu (2020) [ 22 ] MFCCs, time domain and, 150 Rec=96.9 Spe=96.8 non-linear measurements/TabNet network Acc=97.0 F1=97.3 Imran et al (2020) [ 23 ] MFCC and PCA/SVM 543 Rec=96.0 Spe=95.2 Acc=95.6 F1=95.6 This study IMF and DWT based features+ 1187 Rec=99.5 Spe=97.3 ReliefF feature selection/SVM Acc=98.4 F1=98.6 This study ResNet50 based deep features+ 1187 Rec=98.5 Spe=97.3 ReliefF feature selection/SVM …”
Section: Discussionmentioning
confidence: 99%
“…They reported that they achieved high performance with five different classification algorithms. Their performance was calculated to have an accuracy value of 97.0% and F1-score value of 62.0% [ 21 ]. Pal and Sankarasubbu proposed a study based on four classes of cough signals: COVID-19, asthma, bronchitis, and healthy.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Imran et al (2020) used a convolutional neural network (CNN) to introduce a new application to perform direct COVID-19 diagnostics based on cough sounds. Moreover, Mouawad et al (2021) showed the robustness of mel-frequency cepstral coefficient (MFCC) features for automatic detection of COVID-19 through cough and sustained vowel, respectively. A small portion of studies on COVID-19 have focused on machine learning (ML)-based voice quality, a topic that has recently come under the scrutiny of researchers.…”
Section: Introductionmentioning
confidence: 99%